Holy pharma! : healthism discourses in a pharmaceutical advertising website : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - Hathaway, Madeleine (Massey University, 2009)
Modern changes in the public health philosophy and government legislation reflect a desire of health for all. The changes support a new healthism ideology that controls the experience and definition of health. Scholars parallel the function of healthism to that of a religion that meets the needs of a modern secular culture. This study examines a pharmaceutical advertising website, taking a social constructionist stance to investigate dominant representations of healthism and any parallels to the values and practices of Western religion. The website selected is published by a pharmaceutical marketing group that has been disseminating health and product information for l0 years. The installment of March-April 2009 was examined in its entirety. A critical discourse analytic approach drawing on Durkheim and Foucault was adopted to analyse texts, images, and videos. Particular attention was given to the similarities and differences of healthism and religion in terms, meanings, subject positioning and function. Results show healthism to parallel religion in its construction as information, instruction and ritual practice. The expert discourse within healthism promotes a morality that parallels and deviates from religious values with a turn toward the value of the self. This expert discourse informs healthism discourses, constructing a doctrine of unquestionable behaviours that legitimate ritualized health practices. When viewed as an integral entity, the form, content, and function of healthism in pharmaceutical advertising takes on the religious connectivity of values, beliefs and practices that underlies all social life. The website is an intense concentration of coercive and symbolic power to inform the institutionalized social system ofs healthism.
Pages 123 and 143 are missing from the original copy.
Keywords: Psychological aspects; Drugs; Advertising